HETEROGENEOUS DETERMINANTS OF INCOME DISTRIBUTION IN EU COUNTRIES: EVIDENCE FROM THE GWR - Gülcü, Yunus (My University, 2025)
This study analyzes the main economic and structural factors affecting income inequality in the 27 member states of the EU for the period 2009-2022 using Geographically Weighted Regression (GWR). Unlike traditional regression methods, GWR makes it possible to reveal the regional and local variability of the determinants of income inequality by taking into account spatial heterogeneities. In this study, the effects of macroeconomic variables, including per capita income, financial development, public expenditure, inflation and trade openness on the Gini coefficient, which is widely used to measure income distribution, are analyzed. The findings emphasize that the determinants of income inequality vary significantly across countries. For instance, the assumed non-linear relationship of the Kuznets curve does not appear to be valid in all EU countries. Financial development and trade openness have been empirically confirmed to increase income inequality. Conversely, the effect of public expenditures on income inequality is lower than expected, raising important questions about the effectiveness of public policies in this area. The effects of inflation on income inequality are heterogeneous across countries. However, it has been revealed that low levels of inflation in the Euro area during the study period have a limiting function on income inequality. Results indicate that economic policies aiming to achieve income justice should be designed by taking into account the specific socio-cultural, institutional and economic structures of countries. Taking regional differences into account is considered to be a critical element for policymakers in targeting a sustainable and fair income distribution at both national and European levels.
Keywords: Growth; Inflation; Financial Development; Income Distribution; Geographically Weighted Regression